Weapons and warfare - Nardo, Don, 1947- (San Diego : Lucent Books ; Detroit : Thomson/Gale, 2004)
Describes war tactics and weapons from the Stone Age to the twenty-first century, discussing their effectiveness and their impact on warfare as a whole, and includes photos and illustrations, sidebars, and an annotated further reading list.
Stone Age warfare and the Native Americans -- Military innovations in the ancient Near East -- Greece and Rome at war: the rise of the West -- Knights and castles in medieval Europe and Japan -- The fast, fierce armies of the Asian conquerors -- Musket and bayonet: linear warfare emerges -- Industrializing the battlefield: the first modern wars -- Crushing ordeal of total warfare: World War II.
Includes bibliographical references (p. 103-105) and index.
8.9
5-8
Keywords: Military weapons -- History; War -- History